Processing, Adhesion and Corrosion-inhibiting Properties of Poly[2-methoxy-5-(2’-ethylhexyloxy)-1,4-phenylene vinylene], (MEH-PPV) on Aerospace Aluminum Alloys - Zarras, Peter; Buhrmaster, Diane; Stenger-Smith, John D.; Webber, Cindy; Anderson, Nicole; Goodman, Paul A.; Davis, Matthew C. (Journal of Coating Science and Technology, 2021)
Researchers at the Naval Air Warfare Center Weapons Division (NAWCWD) and Wright-Patterson Air Force Base (WPAFB) investigated poly[2-methoxy-5-(2’-ethylhexyloxy)-1,4-phenylene vinylene], (MEH-PPV) for its potential corrosion-inhibition properties on aerospace aluminum alloy AA2024-T3. Solution processing of the polymer, as well as adhesion testing and accelerated weathering tests were performed on MEH-PPV full military aerospace coatings. Wet and dry tape adhesion testing, as well as pencil hardness, impact flexibility and pneumatic adhesion tensile test instrument (PATTI) testing were used to demonstrate the adhesion performance of MEH-PPV on aluminum substrates. The results showed that MEH-PPV had acceptable adhesion characteristics when compared to hexavalent chromium (Cr(VI)) based coatings in all of these tests. Accelerated weathering analysis was performed on MEH-PPV coatings to determine their corrosion protection and weathering resistance capabilities. These tests included neutral salt spray (NSS) exposure and xenon-arc lamp testing. The results showed that while MEH-PPV does not exhibit significant color change after 500 hours of xenon arc lamp exposure, the polymer has poor corrosion protection performance under aggressive salt environments.